Percutaneous Nephrolithotomy Using Split Amplatz Sheath: A Randomized Clinical Trial - Tabibi, Ali; Abedi, Amir Reza; Radfar, Mohammad Hadi; Kamranmanesh, Mohammad Reza; Karami, Hormoz; Arab, Davood; Pakmanesh, Hamid (Urology Journal, 2016)
Purpose: To compare the outcome of percutaneous nephrolithotomy (PCNL) using split or intact Amplatz sheath. Materials and Methods: Seventy two patients who underwent PCNL were randomly divided into two groups; PCNL using intact (group 1) and split (group 2) Amplatz sheath. Preoperative data, operative time, largest extracted stone size, fluoroscopy and lithotripsy time, and serum biochemistry tests before and after PCNL were evaluated. Results: Preoperative features and stone size were not significantly different between the groups. There were no significant differences in complications and postoperative changes in hemoglobin and serum electrolytes. Stone free rate in group 2 (88.1%) was insignificantly higher than group 1 (83.3%) (p = .05), but in staghorn stones and stones larger than 1000 mm2, stone free rate in group 2 was significantly higher than group 1 (82% vs. 72%). The mean extracted stone size in group 2 (150 ± 49) was significantly larger than group 1 (40 ± 16 mm2) (p < .005). The mean operative, lithotripsy and fluoroscopy times were significantly longer in group 1. Conclusion: Using split Amplatz sheath in PCNL facilitates extraction of larger stone fragments which could contribute to shorter fluoroscopy, lithotripsy and operative times.